"Solution"Here, given equation is:
"p(1+q^2)=q(z-a)\\\\\n\\therefore p+pq^2)=qz-qa\\\\\n \\implies p+pq^2-qz+qa=0---(1)"Therefore the Charpit's auxiliary equation is
"\\frac{dp}{\\frac{df}{dx}+p\\frac{df}{dz}}=\\frac{dq}{\\frac{df}{dy}+q\\frac{df}{dz}}=\\frac{dz}{-p\\frac{df}{dp}-q\\frac{df}{dq}}=\\frac{dx}{-\\frac{df}{dp}}=\\frac{dy}{-\\frac{df}{dq}}=\\frac{dF}{0}" or
"\\frac{dp}{0+p(-q)}=\\frac{dq}{0+q(-q)}=\\frac{dz}{-p-pq^2}=\\frac{dx}{-1-q^2}=\\frac{dy}{-2pq-z}=\\frac{dF}{0}"
or
"\\frac{dp}{-pq}=\\frac{dq}{-q^2}=\\frac{dz}{-p-pq^2}=\\frac{dx}{-1-q^2}=\\frac{dy}{-2pq-z}=\\frac{dF}{0}"
So that
"\\implies \\frac{dp-dq}{-pq+q^2}=\\frac{dy-dx}{-2pq-z+1+q^2}\\\\\n\\implies \\frac{dp-dq}{-pq+q^2}=\\frac{dy-dx}{-pq+q^2}\\\\\n\\implies dp-dq = dy-dx\\\\\n\\therefore dp+dx=dy+dq\\\\"
Integrating, we get
"\\implies p+x=y+q\\\\\n\\implies p=y-x+q\\\\"
From equation (1), we get
"p+pq^2-qz+qa=0 \\implies p=pq^2-qz+qa\\\\\n q(pq-z-a)=p\\\\\nq=p\\ or\\\\\nq=\\frac{z-a}{p}"
Using the value "p" and "q" in "dz=pdx+qdy"
"\\implies dz=(y-x+q)dx+(\\frac{z-a}{p})dy\\\\\n\\implies \\frac{dz}{z}=(y-x+q)dx+(\\frac{z-a}{p})dy"
Integrating, we get
"log\\ z=yx+qx-\\frac{x^2}{2}+\\frac{y-ya}{py}"
Comments
Leave a comment